2011
DOI: 10.1007/s13313-011-0104-4
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of selected Puccinia triticina races in South Africa

Abstract: Microsatellite analysis of ten South African races of Puccinia triticina, the causal organism of leaf rust of wheat (Triticum aestivum), divided the population into two groups sharing 32% genetic similarity. In the first group, race 3SA145 (Agricultural Research Council notation) clustered with 3SA122 and 3SA125, two races that have not been detected recently. This grouping was supported by avirulence for Lr1 in all three races. The second group included the current dominant race 3SA133, that shared 42% geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The higher virulence found for 3SA144 (SDDN), collected from triticale in the Western Cape SA during 2005, towards the international and local set of triticale germplasm entries is in strong support with earlier findings of increased virulence for this Pt race towards triticale (Pretorius and Bender 2010). Using microsatellite analyses, Visser et al (2011) found that 3SA144, with added virulence for Lr32, is closely related to four other South African Pt races, namely 3SA132 (SDDJ), 3SA134 (SBD), 3SA137 (SCDS) and 3SA140 (SFDS). Race 3SA145 collected from wheat during the 2009 rust survey season was the first South African Pt race with virulence for Lr37 combined with virulence for Lr12 and Lr13 (Terefe et al 2011).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The higher virulence found for 3SA144 (SDDN), collected from triticale in the Western Cape SA during 2005, towards the international and local set of triticale germplasm entries is in strong support with earlier findings of increased virulence for this Pt race towards triticale (Pretorius and Bender 2010). Using microsatellite analyses, Visser et al (2011) found that 3SA144, with added virulence for Lr32, is closely related to four other South African Pt races, namely 3SA132 (SDDJ), 3SA134 (SBD), 3SA137 (SCDS) and 3SA140 (SFDS). Race 3SA145 collected from wheat during the 2009 rust survey season was the first South African Pt race with virulence for Lr37 combined with virulence for Lr12 and Lr13 (Terefe et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Race 3SA145 collected from wheat during the 2009 rust survey season was the first South African Pt race with virulence for Lr37 combined with virulence for Lr12 and Lr13 (Terefe et al 2011). Based on results from microsatellite analyses as well as the avirulence/virulence profile of 3SA145 and the similarity of the latter with other international leaf rust races, Visser et al (2011) did not exclude the possibility of 3SA145 being an exotic introduction into SA. The avirulence/virulence profile of 3SA248 and supportive microsatellite analyses strongly support the development of this race from 3SA145 (Boshoff et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tritici (Zhang et al, 2010) that are adapted to triticale have been detected. Based on microsatellite analysis, Visser et al (2012) concluded that a race of P. triticina isolated from triticale probably arose via mutation in an existing race. According to Hovmøller et al (2016), an aggressive race of P. striiformis f. sp.…”
mentioning
confidence: 99%
“…The current South African Pt population consists of two primary genetic lineages 20 , but at least five were evident according to Pt isolates collected during the previous century 49 . Three of these appear to be extinct while only one lineage is expanding.…”
Section: Genetic Analysis Of Puccinia Isolatesmentioning
confidence: 99%